2009
DOI: 10.1089/jop.2009.0007
|View full text |Cite
|
Sign up to set email alerts
|

Central Corneal Thickness During Treatment With Travoprost 0.004% in Glaucoma Patients

Abstract: Topical therapy with the prostaglandin derivate travoprost is accompanied by a significant reduction of CCT within one year of treatment. Further clinical studies are needed to evaluate the possible long-term effects of prostaglandins on the CCT of glaucoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
0
26
0
1
Order By: Relevance
“…Furthermore, no significant correlation was found between CCT loss and IOP reduction in the NTG group (r = 0.16, P = 0.32), which is consistent with previous studies. 25,26 Based on Ehlers' IOP correction formula, we expected 0.61 mmHg of IOP underestimation for a CCT reduction of 8.6 mm, which accounts for 20% of the total IOP reduction (3.07 mmHg) observed after 60 months of latanoprost treatment. Presumably because the IOP-lowering effects of latanoprost exceeded the effect of CCT reduction, IOP reduction seemed not to affect CCT thinning in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, no significant correlation was found between CCT loss and IOP reduction in the NTG group (r = 0.16, P = 0.32), which is consistent with previous studies. 25,26 Based on Ehlers' IOP correction formula, we expected 0.61 mmHg of IOP underestimation for a CCT reduction of 8.6 mm, which accounts for 20% of the total IOP reduction (3.07 mmHg) observed after 60 months of latanoprost treatment. Presumably because the IOP-lowering effects of latanoprost exceeded the effect of CCT reduction, IOP reduction seemed not to affect CCT thinning in our study.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, prolonged exposure to prostaglandin analogues seems to induce structural changes at the level of the corneal stroma, and numerous studies have revealed that chronic treatment with prostaglandins reduces central corneal thickness. 15,[19][20][21] This could also affect the results obtained when translated to the real situation of the treatment of patients with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…19 There was no correlation between magnitude of CCT reduction and the measured reduction in IOP, whereas there was a correlation between magnitude of CCT reduction and baseline CCT. 19 Hatanaka et al observed a significant CCT reduction after monotherapy with latanoprost, travoprost and bimatoprost during an eight-week FIGURE 4 Linear analysis of the relationship between CCT reduction and IOP lowering after 12 months of treatment with tafluprost. No significant correlation was observed between these two variables (Pearson, r = 0.145, p = 0.15).…”
Section: Discussionmentioning
confidence: 81%